Records Of The Colony Of New Plymouth In New England Page 177, Image 183 (1856) - (:unkn) unknown (General Publisher, 1675)
that whoever shall shoot of any gun on any necessary occasion, or at any game whatsoever, except at an Indian or a wolf, shall forfeit five shillings for every such shot, till further liberty shall be given.
--
Keywords: DISCHARGE